Enhancing Diagnostic Accuracy in Body Packing Cases: The Impact of Preliminary Diagnosis Awareness on Computed Tomography Evaluation - Taş, Hakan Gökalp; Çetin, Türkhun; Ece, Bünyamin; Çelik Aydın, Özlem; Aydın, Sonay (New Trends in Medicine Sciences, 2024)
Objective: Body packing refers to the concealment of illegal substances within the body. This study aims to evaluate the computed tomography (CT) findings of body packing cases, and to assess whether considering the possibility of body packing in preliminary diagnosis will affect the accuracy of specialists evaluating in the emergency and intensive care departments. Materials and Methods: 20 body packing cases were retrospectively examined for the presence of foreign bodies. A control group was created from 20 non-contrast abdominal CT images. Re-evaluation involved four radiologists. Before evaluating, two radiologists were advised they could be body packers. Results: In 18 (90%) of 20 body packers, foreign bodies were visible in the intestinal lumen, mostly 14 (70%) in the colon. Radiologists who were given preliminary diagnosis, correctly identified all 18 (100%) intestinal foreign body cases and did not make any false positives. Two other radiologists correctly identified 16 (88.9%) cases and missed 2 (11.1%) cases and there was significantly difference (p
Keywords: Anesteziyoloji; Anaesthesiology; Body Packing; Computed Tomography; Pre-Diagnosis; Foreign Bodies / diagnosis; Drug Trafficking; Gastrointestinal Tract